2012
DOI: 10.3892/etm.2012.877
|View full text |Cite
|
Sign up to set email alerts
|

Functional sensory function recovery of random-pattern abdominal skin flap in the repair of fingertip skin defects

Abstract: The fingertip skin defect is a common hand injury often accompanied by tendon or bone exposure, and is normally treated with flaps. The aim of this study was to evaluate the functional sensory recovery of random-pattern abdominal skin flap in the repair of fingertip cutaneous deficiency. A total of 23 patients, aged between 18 and 50 years (mean age, 31 years) with fingertip cutaneous deficiency (30 digits) were treated with random-pattern abdominal skin flaps. The post-debridement defect area measured from 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 12 publications
1
18
0
1
Order By: Relevance
“…It would be prudent to restore sensory function when suturing the superficial radial nerve and the digital nerve (22). In previous studies, the flap nerve was directly sutured with the digital nerve stump, whereas the result was not satisfactory, especially for two-point discrimination test (9)(10)(11)(12)(13)(14). Similar findings were obtained in the present case report, though the thumb flap two-point discrimination was partially restored.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It would be prudent to restore sensory function when suturing the superficial radial nerve and the digital nerve (22). In previous studies, the flap nerve was directly sutured with the digital nerve stump, whereas the result was not satisfactory, especially for two-point discrimination test (9)(10)(11)(12)(13)(14). Similar findings were obtained in the present case report, though the thumb flap two-point discrimination was partially restored.…”
Section: Discussionsupporting
confidence: 77%
“…These flaps can be raised as adiposal-only flaps or extended flaps and supercharged through perforator-to-perforator anastomoses. For traumatic fingertip and finger stump reconstructions, digital artery perforator flaps deliver consistent aesthetic and functional results (7)(8)(9). Subsequently, numerous clinical trials have demonstrated that the thumb dorsoulnar artery pedicle flap is an effective technique to repair soft tissue defects (7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fingertip defect, one of the most common injuries in the hand, is treated with various flaps such as random pattern abdominal flap and retrograde digital artery island flap. 1 2 3 4 5 However, swelling in the fingertip, dysfunction of sensation and scarring leads to restriction of flexion and extension. Injury to the hemi-artery of the finger usually occurs during the recovery stage.…”
Section: Introductionmentioning
confidence: 99%
“…Все пациенты завершили исследова-ние в конце шестого месяца. Авторы проводили также морфологическое исследование препара-тов из лоскутов в различные периоды, обнару-жив разные стадии восстановления нервных окончаний и телец Пачини, Руффини и колб Краузе, отвечающих за определенные виды чув-ствительности [165]. По данным S. Woo и соавт.…”
Section: № 1 (56) март'2016unclassified